I Open Fire - Pol, David (punctum books, 2014)
David Pol presents an ontology of war in the form of the lyric poem. "Do you hear what I'm shooting at you?" In I Open Fire, all relation is warfare. Minefields compromise movement. Intention aims. Touch burns. Sex explodes bodies. Time ticks in bomb countdowns. Sound is sirens. Plenitude is debris. All of it under surveillance. "My world is critically injured. It was ambushed." The poems in this book perform the reductions and repetitions endemic to war itself, each one returning the reader to the same, unthinkable place in which the range of human experience has been so flattened that, despite all the explosive action, "Almost nothing is happening." Against this backdrop, we continue to fall in love. But Pol's poems remind us that this is no reason for optimism. Does love offer a delusional escape from war, or are relationships the very definition of combat? These poems take up the themes of love, sex, marriage, touch, hope - in short, the many dimensions of interpersonal connection - in a world in unprecedentedly critical condition. "And when the night goes off the shock wave throws us apart toward each other."